Guideline for Development of Learning Management for Teachers in School Network of Kok Sa-Ard Sub-District, Chaiyaphum Primary Educational Service Area Office 2 - Buapong, Panisara (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aims to 1) examine the current and desired states of teachers’ learning management in schools under Khok Sa-at Subdistrict, Office of Chaiyaphum Primary Educational Service Area 2, and 2) develop practical guidelines for enhancing teachers’ learning management. The sample consisted of 63 teachers and administrators. The research instruments included a five-point rating scale questionnaire, interviews, and feasibility and appropriateness assessment forms. Data were analyzed using percentage, mean, standard deviation, and the Modified Priority Needs Index (PNImodified). The results revealed that: 1. The current state of learning management consists of five key components: curriculum development, learning activity management, assessment and evaluation, teacher characteristics, and the use of media and technology-all of which are essential elements for instructional improvement. The desired state was rated at the highest level, with the highest needs in media and technology utilization, followed by teacher characteristics, learning activity management, assessment and evaluation, and curriculum development. 2. The proposed guidelines for learning management include 35 strategies across five domains: integration of media and technology (7 strategies), enhancement of teacher characteristics (7 strategies), improvement of assessment and evaluation (7 strategies), development of learning activities (7 strategies), and curriculum development (7 strategies). All strategies were validated for suitability, feasibility, and applicability to enhance instructional practices within the schools.